2007
DOI: 10.1136/jnnp.2006.095612
|View full text |Cite
|
Sign up to set email alerts
|

Moderate therapeutic efficacy of positron emission tomography-navigated repetitive transcranial magnetic stimulation for chronic tinnitus: a randomised, controlled pilot study

Abstract: Background: Tinnitus has been shown to respond to modulations of cortical activity by high-frequency and low-frequency repetitive transcranial magnetic stimulation (rTMS). Objective: To determine the tinnitus-attenuating effects of a 2-week daily regimen of rTMS, navigated to the maximum of tinnitus-related increase in regional cerebral blood flow. Methods: Six patients with chronic tinnitus were enrolled in this sham-controlled crossover study and treated with 262 weeks of suprathreshold 1 Hz rTMS (30 min) ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
124
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(133 citation statements)
references
References 36 publications
8
124
1
Order By: Relevance
“…The study of Khedr et al [2008] showed a positive effect of rTMS and treated a population with a fairly short tinnitus duration; the greatest proportion of patients had a duration (much) shorter than 4.5 years. A shorter duration of tinnitus has been observed to have a positive effect on treatment outcome [de Ridder et al, 2005;Khedr et al, 2008;Kleinjung et al, 2007;Plewnia et al, 2007b], although other studies do not find this effect [Lehner et al, 2012;Smith et al, 2007], including 1 study [Lehner et al, 2012] correcting for possible confounding effects. The study of Marcondes et al [2010] showed a positive effect of rTMS and was performed only on normally hearing subjects.…”
Section: Bilateral Rtms For Tinnitusmentioning
confidence: 88%
See 1 more Smart Citation
“…The study of Khedr et al [2008] showed a positive effect of rTMS and treated a population with a fairly short tinnitus duration; the greatest proportion of patients had a duration (much) shorter than 4.5 years. A shorter duration of tinnitus has been observed to have a positive effect on treatment outcome [de Ridder et al, 2005;Khedr et al, 2008;Kleinjung et al, 2007;Plewnia et al, 2007b], although other studies do not find this effect [Lehner et al, 2012;Smith et al, 2007], including 1 study [Lehner et al, 2012] correcting for possible confounding effects. The study of Marcondes et al [2010] showed a positive effect of rTMS and was performed only on normally hearing subjects.…”
Section: Bilateral Rtms For Tinnitusmentioning
confidence: 88%
“…Six randomised crossover studies have been performed on small patient groups ( table 1 ), half of them showing a positive effect [Kleinjung et al, 2005;Plewnia et al, 2007a;Rossi et al, 2007] and the other half of them showing no (significant) effect [Piccirillo et al, 2011;Plewnia et al, 2007b;Smith et al, 2007]. On average, these studies combined showed a decrease of 4 points on the TQ (20 patients) [Kleinjung et al, 2005;Plewnia et al, 2007b], an improvement on the THI of 4 points compared with placebo (14 patients) [Piccirillo et al, 2011], and a general VAS score improvement of 11 points compared with placebo (20 patients) [Rossi et al, 2007;Smith et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…There is no certain method or pharmacological agent for the treatment of tinnitus, which is due to the uncertainty in the etiology of tinnitus 7 . Tinnitus, which affects 17% of the general population, is the primary complaint experienced by 60% of patients in the field of audiology 8 .…”
mentioning
confidence: 99%
“…The fact that the study by Plewina et al (16) included only 6 patients does not in our view undermine its "validity" as Hicks et al point out. A crossover design as applied in this study enhances statistical power (17).…”
Section: Replymentioning
confidence: 56%